2018
DOI: 10.3988/jcn.2018.14.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Common Carotid Artery after Radiotherapy: Wall Thickness, Calcification, and Atherosclerosis

Abstract: Background and PurposeSince the long-term survival rate has improved in laryngeal cancer patients who receive radiotherapy, concerns about postradiation complications (including carotid atherosclerosis) have increased. We followed changes in the common carotid artery (CCA) after radiotherapy and identified the underlying risk factors.MethodsConsecutive patients with laryngeal cancer who underwent radiotherapy between January 1999 and December 2009 and who had received computed tomography (CT) both pre- and pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 24 publications
3
14
0
Order By: Relevance
“…Few longitudinal studies include measurements before RT and those have a maximal follow-up of 2 years [8,12]. While a continuous progression was observed in one study [12], no change could be observed in another one [8]. The present analysis with a maximal follow-up of 4.5 years supports an initial increase in intima media thickness, though no major development could be observed after about one year (Fig.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…Few longitudinal studies include measurements before RT and those have a maximal follow-up of 2 years [8,12]. While a continuous progression was observed in one study [12], no change could be observed in another one [8]. The present analysis with a maximal follow-up of 4.5 years supports an initial increase in intima media thickness, though no major development could be observed after about one year (Fig.…”
Section: Discussionsupporting
confidence: 52%
“…Most of these results, however, are based on cross-sectional studies. Few longitudinal studies include measurements before RT and those have a maximal follow-up of 2 years [8,12]. While a continuous progression was observed in one study [12], no change could be observed in another one [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They were found in all segments of the carotid arteries, primarily in the CCA and proximal segments of the ICA and ECA. A remarkable variation of radiological symptoms and the multifocal appearance of radiation-induced vascular diseases have been also reported in the literature [11], [18], [19].…”
Section: Discussionmentioning
confidence: 68%